Benefits of Ultrasond, Tens and Hold Rilex Streching in Osteoarthritis Genu Dextra: A Case Study - Khairunissa, Hatifa; Hidayati, Ina; Naufal, Adnan Faris; Setyawan, Agus (Academic Physiotherapy Conference Proceeding, 2023)
Introduction: Osteoarthritis is a progressive, degenerative joint disease in which the cartilage that protects the ends of the bones begins to break down, accompanied by reactive changes at the joint edges and subchondral bone that cause pain and loss of movement.Based on the results of health research on the basis of Riskesdas in 2013, the prevalence of joint disease based on health diagnoses in Indonesia was 11.9% and 24.7% based on symptoms. The highest prevalence based on diagnosis by health workers was in Bali 19.3% while based on symptoms the highest was in East Nusa Tenggara 33.1%, West Java 32.1%, DKI Jakarta 21.8% when viewed from age characteristics, the highest prevalence was at age ≥ 75 years (54.8%) there were also more female patients (27.5%) compared to men (21.8%). Case Presentation: A 56 year old man came to RSJD Dr. Arif Zainuddin Surakarta with complaints of pain in the right knee and could not fully bend because he had experienced a fall and slipped on the right knee. He has hypertension, diabetes and cholesterol. On physical examination with vital signs heart rate 99 beats/minute, respiration 20 beats/minute, blood pressure 170/100 mmHg with a height of 155 cm and a weight of 74 kg. From the static inspection examination found edema and dynamic inspection it was seen that he walked slowly and endured a little pain and seemed to be using a tripod. Results : From the examination of pain using a vase on the right knee, the results were: silent pain (2), motion pain (4), tenderness (4). Measuring muscle strength with MMT on the right knee with flexion extension movement obtained 4 results. Anthropometric examination of the odema using the mid line with the results of the right knee (42 cm), left knee (36.5 cm) which means a difference of 5.5 cm. Then a special examination was carried out on OA using the Jette scale and measuring the LGS with a goniometer Conclusion : After using ultrasound, electrical stimulation, hold rilex in the Osteoarthritis Genu Dextra Case with Ultrasound, Electrical Stimulation and Exercise at RSJD Dr. Arif Zainuddin Surakarta isA patient with a diagnosis of osteoarthritis, male, 56 years old, was given physiotherapy treatment for two treatments from June 26 2023 to July 4 2023. The problems with physiotherapy were found to be pain, decreased strength of the right knee muscles, edema on the knee dextra and decreased functional activity. After being treated twice, the results showed that there was no increase in MMT in the knee flexor-extensor muscles, there was no decrease in tenderness, silent pain, and motion pain, but there was a decrease in dextra knee edema, and there was no increase in functional activity.